ANTECEDENTS OF CUSTOMER SATISFACTION IN FOOD SERVICE BUSINESS (A REVIEW) - Rafael Modestus Ziku; Liesiana Kurniawati; Febi Marice Erni Utan; Adrianus Nabung (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2019)
This study presents literature review relating to antecedents of customer satisfaction in food service business. The review is based on literatures about customer satisfaction in food service related business that have been published in peer reviewed journals in the period from 2012 to 2016. A total of 17 articles were reviewed. Through a systematic review process, the result of this study shows there are three major antecedents of customer satisfaction in food service related business, namely quality of service, food attributes, and atmospheric factors